Rupture of a superficial temporal artery pseudoaneurysm following craniotomy. Issue 9 (8th September 2021) - Shields, Jessica; Robichaux, Jared; Morrow, Kevin; Crutcher, Clifford; Tender, Gabriel
Abstract: Pseudoaneurysm of the superficial temporal artery (STA) is a rare entity that has been reported in the literature after trauma or iatrogenic injuries. We describe a unique case of STA pseudoaneurysm rupture and the clinical sequelae associated with its rupture. We report a case of pseudoaneurysm rupture of the STA that occurred 14 days after craniotomy for cerebrospinal fluid leak repair. We also review the literature, diagnosis and treatment of external carotid artery aneurysms. Rupture of a STA pseudoaneurysm is a previously unreported and serious complication that must be quickly recognized in order to control hemorrhage that may have life threatening complications.